Characterization of silica supported chromium complexes - Parentis, Monica Liliana (2000)
The Cr/SiO2 catalysts were prepared via the deposition of mononuclear and binuclear chromium (III) ammine complexes on silica. The influence of chromium loading and calcination temperatura upon the type of species formed was determined. FTIR and Raman studies revealed the presence of Cr(VI) species as monomers and dimers in calcined catalysts and the existence of a chemical interaction between the complex chromium ions and the support. Futhemore, IR of adsorbed pyridine showed the presence of Lewis centers just before calcination. After calcination Brönsted sites were developed, these sites were related to the presence of Cr(VI) species. The relative concentration of such centers depends on the ammount of chromium exchanged.